O limite punitivo do doping em face da dignidade da pessoa humana - Zanini, Flavia de Oliveira (2019)
This dissertation aims to study the punitive limit of doping in the face of human dignity. It is observed that sport promotes insertion, social integration, and its purpose is to instigate equality and health. In the case of professional practice, it brings with it the value of work, the financial valuation, safeguards the dignity of the human person, providing the athlete with his or her family and support. In the present study we will address the punitive limit of doping with respect to the professional athlete. To this end, it is necessary to present the institutes and institutions, such as the AMA-WADA - World Anti-Doping Agency, the World Anti-Doping Code, the International Convention against Doping in Sport (UNESCO), the Brazilian Doping Control Authority (ABCD), the Brazilian Doping Control Laboratory (LBCD). Delimited the main aspects about doping, we will bring the multidisciplinary definitions of Human Rights and the principle of human dignity applied to the professional activity of the athlete. Objectifying. It will seek to assess the legal meaning of doping and its consequences in the athlete's professional activity, presenting an analysis of the disciplinary sports sanctions and the banishment of the athlete, their impacts on society, the athlete's life and how much banning hurts the right to review of the Universal Declaration of Human Rights. To carry out the study and achieve the outlined objective, it will be necessary to apply a methodology, whose scientific method is dialectic, and the research will be bibliographic and doctrinal, with qualitative approach